2010
DOI: 10.5539/gjhs.v2n2p225
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study on Awareness Regarding Safe and Hygienic Practices amongst School Going Adolescent Girls in Rural Area of Wardha District, India

Abstract: Onset of menstruation is one of the most important changes occurring during adolescence. In various parts of India, there are several cultural traditions, myths and misconceptions related to menstruation, which make them vulnerable to genital tract infections. To understand the perceptions, source of information and status of menstrual hygiene a cross-sectional study was carried out amongst 300 school going adolescent girls (10-19 yrs) in the rural area of Wardha district, Maharashtra, India.Majority of the gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
101
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 3 publications
13
101
3
1
Order By: Relevance
“…5% and 43.67% reported that they became scared at the moment when menarche happened. 12,13 Also Shubha Dubey observed in her study that 42% of urban and 50% of rural respondent were scared when they had their first menstruation.…”
mentioning
confidence: 99%
“…5% and 43.67% reported that they became scared at the moment when menarche happened. 12,13 Also Shubha Dubey observed in her study that 42% of urban and 50% of rural respondent were scared when they had their first menstruation.…”
mentioning
confidence: 99%
“…4 The hygiene related practices of the study subjects during menstruation was considerably acceptable in contrast to other studies. 3,9,11,12 Clipping of pubic hair was seen in 136 (69%). Frequent (2-3 times) washing of perineal area with water alone was noticed in 104 (52.8%) cases of this segment, with soap and water in 79 (40.20%) and about 14 (7.10%) were washing with Dettol also.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In various parts of India, there are several cultural traditions, myths and misconceptions related to menstruation, which make them vulnerable to genital tract infections. According to a study by Mudey et al in Wardha district, India (2010), [2] menstruation is generally considered unclean leading to isolation of the menstruating girls and restrictions imposed on them by the family. In India, certain taboos are followed, for example once the menstruation begins the girl is isolated from participating in day to day activities, first she should take a bath as soon as she wakes up from sleep for which there is a separate place where she has to take a separate mat for sleeping which should be washed every day.…”
Section: Introductionmentioning
confidence: 99%